PENERAPAN DIGITAL MARKETING DALAM MENINGKATKAN EFESIENSI DAN PROFITABILITAS PADA PT WAHYU WAHANA CARGO - Kusuma Wijaya, Komang Ari; Suparna, Putu (Asawika : Media Sosialisasi Abdimas Widya Karya, 2025)
This Field Work Practice (PKL) was conducted at PT Wahyu Wahana Cargo with the objective of analyzing the effectiveness of email marketing campaigns in acquiring new customers and retaining existing ones. The study employed both quantitative and qualitative approaches, focusing on key metrics such as open rate, click- through rate, conversion rate, and customer retention. Initial observations revealed that the company’s mass email campaigns to 385 businesses resulted in a low engagement rate, with an open rate of 24.9% and a click rate of 7%. To address these challenges, improvements were implemented, including database segmentation, personalized content, and A/B testing. A trial campaign sent to 35 companies demonstrated a significant increase in performance, achieving an open rate of 85% and a click rate of 85.7%. Furthermore, personalized emails based on transaction history strengthened long-term customer relationships, while LinkedIn was explored as an additional channel to expand B2B customer acquisition. The findings highlight that structured email marketing strategies, supported by personalization, data-driven testing, and omnichannel integration, can substantially enhance both customer acquisition and retention in the logistics industry. Keywords: Email Marketing, Customer Acquisition, Customer Retention, Logistics, Digital Marketing